Involving stakeholders in scenario-building: Lessons from a case study of the global context of Norway’s climate policies - Fæhn, Taran; Stoknes, Per Espen (Frontiers in Environmental Science, 2023)
This paper assesses the relevance and outcome of involving a transdisciplinary group of stakeholders in a scenario-building research project. The scenarios describe plausible external, long-term conditions with the aim to improve the knowledge basis of a national (Norwegian) government pursuing climate policy targets for 2030 and 2050 under uncertainty. The scenario process has two phases with quite different roles for the participants. In the first, the aim is to create broad engagement and participation in exploring narratives for how key external conditions might develop and form premises for the national climate strategies for Norway. The ambition in this phase is to deduce a handful of wide-ranging and distinctly different, qualitative scenarios. The second phase is devoted to translating the narratives into quantitative projections for the Norwegian economy and greenhouse gas emissions by means of linking global and national largescale models. We claim that research projects building and using scenarios have significant potential to benefit from involving a broad stakeholder group in developing qualitative narratives. The second phase involves complex quantitative simulations. In order to provide scientific rigor and credibility to the scenarios, this phase primarily calls for scholars with technical skills, knowledge on the research frontier and modelling experience. Nevertheless, later use of these scenarios in numerical policy studies can gain from resumed researcher-stakeholder interaction.